Credit scoring model for Vietnamese non-manufacturing companies :A thesis submitted as a requirement for the degree of Bachelor of Finance and Banking/Đào Thu Hằng ; Đào Thanh Bình supervisor. - Đào, Thu Hằng.
Khoá luận tốt nghiệp.